Asuhan Kebidanan Komprehensif pada Ny. R, 28 Th, G2P1A0 dengan Keputihan Fisiologis di Puskesmas Bandaran Kecamatan Tlanakan Kabupaten Pamekasan Tahun 2022 - Lianita Primi Octaviana; Raudlatul Jannah (Ovary Midwifery Journal, 2023)
Pregnancy is a normal thing to happen to a woman, which at this time involves physical and emotional changes. During pregnancy there are hormonal changes that occur in the mother, resulting in an inconvenience in the mother, for example vaginal discharge. Basically, vaginal discharge that occurs in pregnant women is a physiological thing if there is no change in color, smell and itching.. Fluor albus or commonly called vaginal discharge is a large amount of vaginal secretion with a thick or liquid contingency starting from the first trimester, but will increase more in the second trimester and III trimester, as a form of vaginal mucosal hyperplation. Although this is a physiological thing, it still makes people, especially pregnant women, feel worried. The purpose of this study was to conduct Comprehensive Obstetric Care in Mrs.R, 28 Years, G2P1A0 with Physiological Whiteness at the Puskesmas Bandaran, Tlanakan District, Pamekasan Regency. This study was conducted from January to April 2022 with a descriptive method, namely by following the patient's progress using countinue of care from pregnancy to birth control. From the results of the examination given to Mrs. "R" 28 Years G2P1A0 it was found that the mother experienced complaints of vaginal discharge which is a physiological thing due to hormonal changes and blood flow in the uterine and vaginal areas, which resulted in an increase in the process of vaginal secretion and these hormonal changes can also change the balance of vaginal acidity, causing the appearance of yeast and usually not accompanied by itching and discoloration, the mother has been given HE to lock properly from front to back, dried with tissue or towel, avoid using tight underwear, immediately change underwear if it feels damp so that the complaint is resolved.